The analytical method of kick thrust like a propeller in breaststroke - Takeshima, Y. (Japanese Journal of Sciences in Swimming and Water Exercise, 2014)
Kicking like a propeller in breaststroke is nowadays widely used by breaststrokers. Maglischo5) explains that a breaststroker kicks until legs are stretched straightly to generate thrust, drawing a semicircle with both legs like a propeller. It is said that the breaststroke kick like the propeller is supposed to generate big thrust. But in the process of this study, the calculation result of propeller-like kick thrust revealed that enough thrust does not occur in the usual propeller theory. It seems that the application of Dynamic Stall is to be supposed to generate enough thrust to apply the second law of Newton. The purpose of this study is to obtain the method for the analysis of this big thrust using Dynamic Stall.